Cross-Cultural Design. Applications in Health, Learning, Communication, and Creativity c - Rau, Pei-Luen Patrick; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This two-volume set LNCS 12192 and 12193 constitutes the refereed proceedings of the 12th International Conference on Cross-Cultural Design, CCD 2020, held as part of HCI International 2020 in Copenhagen, Denmark in July 2020. The conference was held virtually due to the corona pandemic. The total of 1439 papers and 238 posters included in the 40 HCII 2020 proceedings volumes was carefully reviewed and selected from 6326 submissions. The regular papers of Cross-Cultural Design CCD 2020 presented in this volume were organized in topical sections named: Health, Well-being and Social Design Across Cultures, Culture, Learning and Communication, and Culture and Creativity.
Health, Well-being and Social Design Across Cultures -- Culture, Learning and Communication -- Culture and Creativity. .
Keywords: User interfaces (Computer systems).; Human-computer interaction; Coding theory; Information theory; 9; Computers, Special purpose; Social sciences -- Data processing; Education -- Data processing; User Interfaces and Human Computer Interaction; Coding and Information Theory; Computer Communication Networks; Special Purpose and Application-Based Systems; Computer Application in Social and Behavioral Sciences; Computers and Education